Cambios en cobertura y regeneración arbórea en bosques siempreverdes en diferentes estados sucesionales en el sitio experimental de Llancahue, Cordillera de la Costa de Valdivia, Chile - DONOSO, PABLO J.; PONCE, DIEGO B.; PINTO, JOSELYN B.; TRIVIÑO, IVÁN L. (Gayana Botánica, 2018)
In the Llancahue experimental site (39°50’; 300-400 m) we evaluated richness of tree and understory species in an old-growth forest and in two secondary forests. Having similar species’ richness in these forests, the study supports our hypothesis that this is a result of successional development and natural and anthropogenic disturbances.